The effect of roa, roe and roi on company value - Arda Raditya Tantra; Dewi Ari Ani; Fitri D Jayanti (The Accounting Journal of Binaniaga, 2021)
The purpose of th.is study was to study financial performance using the ratio of Return On Asset (ROA), Return On Equity (ROE), and Return On Investment (ROI) with the value of a company's Price Book Value (PBV) in the banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2016-2019. The met.hod used in this study is a quantitative descriptive method. The data used in this study is secondary data obtained from the company's financial performance statements. The technique used in this study is the purposive sampling technique. While the data analysis used in this study is multiple linear regression, coefficients, and determination using calculation tools using SPSS. The results of this study refer to the analysis of financial performance with profitability ratios, namely Return On Assets (ROA), Return On Equity (ROE), Return On Investment (ROI) impacting the company's value of Price Book Value (PBV).Keywords : ROA, ROE, ROI, PBV